Improving data concerning women's empowerment in sub-Saharan Africa - Heckert, Jessica; Fabic, Madeleine Short (Wiley, 2013)
This study assesses the utility of Demographic and Health Survey (DHS) questions regarding women's empowerment in the context of sub‐Saharan Africa. We examine the use of, and need for improvements to, women's empowerment data in Ghana, Mozambique, Senegal, and Uganda. Drawing on interviews conducted among gender and health experts and on context‐specific literature, our findings reveal that although DHS data are widely used, data needs remain in five areas: economic empowerment, knowledge of legal rights and recourse, participation in decisionmaking, attitudes and social norms, and adolescent girls. We recommend that Demographic and Health Surveys be modified—for example, through adding specific survey items—to fulfill some but not all of these emerging women's empowerment data needs. We also suggest that other surveys fill known gaps and that data users carefully consider the meaning and relative weight of the women's empowerment items according to the cultural context in which the data are collected.